Answer:
The proof is given below.
Step-by-step explanation:
Let the measure of angle A be
and B be
.
Now, from the triangle ΔABC,
![m\angle A+m\angle B+m\angle C=180\\2x+2y+m\angle C = 180\\2(x+y)=180-m\angle C](https://tex.z-dn.net/?f=m%5Cangle%20A%2Bm%5Cangle%20B%2Bm%5Cangle%20C%3D180%5C%5C2x%2B2y%2Bm%5Cangle%20C%20%3D%20180%5C%5C2%28x%2By%29%3D180-m%5Cangle%20C)
As angle C is a positive quantity, so,
will be less than 180.
Therefore,
....... 1
Now, for triangle ΔAOB,
Since AO is an angle bisector of
, therefore, ![m\angle OAB = \frac{2x}{2}=x](https://tex.z-dn.net/?f=m%5Cangle%20OAB%20%3D%20%5Cfrac%7B2x%7D%7B2%7D%3Dx)
Similarly, ![m\angle ABO = \frac{2y}{2}=y](https://tex.z-dn.net/?f=m%5Cangle%20ABO%20%3D%20%5Cfrac%7B2y%7D%7B2%7D%3Dy)
Now, sum of all the interior angles of a triangle is 180 degrees.
∴ ![m\angle AOB + m\angle ABO + m\angle OAB=180](https://tex.z-dn.net/?f=m%5Cangle%20AOB%20%2B%20m%5Cangle%20ABO%20%2B%20m%5Cangle%20OAB%3D180)
![m\angle AOB +y+x=180\\m\angle AOB =180-(x+y)](https://tex.z-dn.net/?f=m%5Cangle%20AOB%20%2By%2Bx%3D180%5C%5Cm%5Cangle%20AOB%20%3D180-%28x%2By%29)
Now, consider the inequality 1.
![x+y](https://tex.z-dn.net/?f=x%2By%3C90)
Multiplying by -1 on both sides. This changes the sign of the inequality.
![-(x+y)>-90](https://tex.z-dn.net/?f=-%28x%2By%29%3E-90)
Adding 180 on both sides, we get
![180-(x+y)>180-90\\180-(x+y)>90](https://tex.z-dn.net/?f=180-%28x%2By%29%3E180-90%5C%5C180-%28x%2By%29%3E90)
But, ![180-(x+y)=m\angle AOB](https://tex.z-dn.net/?f=180-%28x%2By%29%3Dm%5Cangle%20AOB)
Therefore,
. Hence, it is proved.